A modified Indirect Matrix Converter with High Voltage Gain for Variable Speed Drive Application - Hweshim, Mohammed Ali Hussein; Hamodat, Zaid; Sadane, Zaid Khalaf Mohammed (Migration Letters, 2024)
For this paper, the literature review can be summarized as follows: QZSN was placed between the transformer phase in IMC and the rectifier phase. Inductor coils were used in the DC link and large capacitors, which increases the cost of the system in general.The non-continuous QZS-IMC technology was used to power the induction motor, and it is necessary to use an additional input filter to avoid harmonic frequencies from the current system. Closed input current control was used to reduce the frequency harmonics of the input current of the continuous intermittent control system to feed the R-L load. ZS/QZS-IMC was used with an R-L load, and the overwork ratio D was fixed at a certain value resulting in continuous boost, which is compatible with the constant voltage system . A method for controlling the maximum voltage of a DC motor closed circuit breaker based on QZS-IMC technology was used to correct the peak voltage value of the DC circuit breaker of an AC motor. As the continuous QZS-IMC was operated with the R-L load during the lowering and lifting modes, there was a control strategy to generate the time duty ratio of the exchange D. Continuous driving based on QZS-IMC technology was not used to drive a permanent magnet AC motor. In this paper, SVPWM was used to control the relays for the qzs-IMC continuous drive system of a carrier-controlled AC motor. A D-value control strategy has also been proposed based on the internal voltage and external voltage required for QZS-IMC to regulate the DC link voltage relative to the required speed and load. This strategy will contribute to reducing the current and voltage stresses of the power switches during voltage increase, by increasing the value of D in order to raise the internal voltage of the AC motor to the required level. Thus, the engine can be started at the required speed and load during various conditions .